Resilience of deep aquifer microbial communities to seasonal hydrological fluctuations - Sébastien Giroud; Longhui Deng; Mark A. Lever; Oliver S. Schilling; Rolf Kipfer (Proceedings of the National Academy of Sciences, 2025)
The influence of seasonal variations in temperature and precipitation on subsurface biogeochemical processes remains poorly understood. In the Lavey-les-Bains thermal system in the Swiss Alps, annual variations in electrical conductivity are observed to depths of 500 m, suggesting a potential link to surface environmental changes. Here we show, through year-round analyses of stable water isotopes, noble gases, and conductivity, that seasonally varying contributions of shallow groundwater from the Rhône alluvial aquifer mix with deep groundwater. Despite vertically similar fluid geochemical compositions suggesting high hydrological connectivity, microbial communities exhibit significant depth-dependent variation with minimal seasonal change. This decoupling of dynamic water source partitioning and stable microbial community structure has not been previously observed and fills a critical gap in our understanding of geothermal systems and microbial life in the deep subsurface. At 200 m, the communities are dominated by sulfur-disproportionating Bacteria ( Dissulfurispira ) and Micrarchaeota, while at 500 m the major groups include sulfate- and iron-reducers and/or hydrogen-oxidizers (Thermales, Thermodesulfobacteriota, and Bathyarchaeota). Our study highlights the resilience of terrestrial subsurface microbial communities to temporal variations in water sources and fluid composition. We propose that intrinsic environmental properties—such as temperature—are more critical drivers of microbial community structure in hydrologically connected deep aquifers than seasonal hydrological changes.